The cardiovascular system at a glance - Aaronson, Philip I.; Connolly, Michelle J.; Ward, Jeremy P. T. (At a glance series (Oxford, England), 2013)
This concise and accessible text provides an integrated overview of the cardiovascular system - considering the basic sciences which underpin the system and applying this knowledge to clinical practice and therapeutics